Fluorescent properties and protein-ligand interactions of boron dipyrromethene molecular rotor - Dudko, Anastasiya; Horetski, Matvey S.; Frolova, Nina S.; Faletrov, Yaroslav V.; Shkumatov, Vladimir M. (Journal of the Belarusian State University. Chemistry, 2022)
A fluorescent molecular rotor (FMR) based on boron dipyrromethene core was obtained. Fluorescence emission properties of the compound strongly depend on the medium viscosity. The emission intensity increases 27 times after viscosity changing from ethanol to glycerol medium. At the same time, the compound appeared almost insensitive to solvatochromic effects. Obtained FMR also can affinely bind with the bovine serum albumin protein active sites followed by noticeable emission intensity growth. Possible ligand binding cites and main amino acid surrounding were described with molecular docking simulations and are in an agreement with experimental data. The results can be used for further design and synthesis of novel fluorescent viscosity and protein-ligand interactions censors suitable for implementation in biosystems in vitro and in vivo.
Keywords: бордипиррометен; бычий сывороточный альбумин; молекулярный докинг; молекулярный ротор; флуоресценция